Measurement of background radiation in Jhapa, Ilam, Panchthar, and Taplejung districts of Nepal - Shrestha, Arun Kumar; Nepal, Roshan; Shrestha, Kamala; Regmi, Dijan; Shrestha, Ganesh Kumar; Shah, Buddha Ram; Koirala, Ram Prasad (BIBECHANA, 2023)
In this study, we investigated the levels of background radiation in different locations across the Eastern part of Koshi province, specifically in Taplejung, Panchthar, Ilam, and Jhapa. We used a portable Geiger Muller counter to collect data from twenty different locations, with five sites taken from each district. The average absorbed dose rate was found to be 0.243±0.035 mSv/y. The highest measured value of absorbed dose was 0.335±0.041 mSv/y at Pathivara temple in Taplejung, and the lowest was found to be 0.197±0.039 mSv/y at Kakarvita, Jhapa. The results suggest that these four districts do not pose any radiation risk because it was below the threshold of risk (1mSv/y). We also measured the variation of absorption dose with altitude which is positively correlated with altitude with a correlation coefficient of +0.57. This might be because of the surge in cosmic radiation with an increase in altitude.